Obtaining and characterization of pellets based on walnut shells, waste paper and paperboard - Perez, Y; Gonzalez, A; Castillo, J; Sanchez, A; Oliveira, P; Pichara, C (Rev. Téc. Fac. Ing. Univ. Zulia, 2019)
Spite of continuously deforestation in Chile in the last 40 years, the production of combustion pellets is increased, being the main producer Ecomas. For this study, it was testedwalnut and wheat shells, waste paperboard and waste Kraft paperas raw materials for17 formulations of pellets. Only 8 formulations were successful for pellet production. The 8 pellets obtained and Ecomas pellet were compared according to ash and moisture content and heating value (HHV). The pellets obtained indicated a better HHV and moisture content but a higher ash content than Ecomas pellet. Moreover, 8 pellets and Ecomas pellet were compared with the set values inEuropean Norm EN 14961-2, indicating that pellets 5 and 6, meet the EN 14961-2. In view of the results achieved, the mixtures used in this study could considered as promising raw material for the production of combustion pellets with similar characteristics as commercial pellet Ecomas.